2018
DOI: 10.1002/admi.201800928
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme‐Free Detection of Glucose with a Hybrid Conductive Gel Electrode

Abstract: Current assays for glucose monitoring rely predominantly on glucose oxidation-catalyzing enzymes because of the high specificity of enzyme-substrate interactions. Enzymes are however expensive, suffer from instability during fabrication, operation and storage, and necessitate complex procedures for integration with transducer materials. These challenges, rendering the enzyme-based sensors disadvantageous for routine glucose monitoring, can be overcome by non-enzymatic sensors. Here, for the enzyme-free detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 49 publications
0
58
0
Order By: Relevance
“…[35][36][37][38] Diabetic patients are advised to keep their blood glucose levels close to the target range below 7 mM (fasting). 39,40 Recent studies have demonstrated a significant positive correlation between the concentration of glucose in saliva and blood for healthy and Fig. 4 a Current-time characteristics of the sensor in response to different concentrations of glucose successively added into saliva.…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37][38] Diabetic patients are advised to keep their blood glucose levels close to the target range below 7 mM (fasting). 39,40 Recent studies have demonstrated a significant positive correlation between the concentration of glucose in saliva and blood for healthy and Fig. 4 a Current-time characteristics of the sensor in response to different concentrations of glucose successively added into saliva.…”
Section: Resultsmentioning
confidence: 99%
“…These promising 2D materials have been utilized to sense chemicals such as heavy metals and hazardous gases through functionalized graphene electrodes Beduk et al, 2020a), pressure and motion based on changes in resistivity (Yamada et al, 2011;So et al, 2013;Ryu et al, 2015;Zhang Y.-Z. et al, 2018), as well as electrophysiological signals and biomarkers like chloride, lactate and glucose through the functionalization of field effect transistors and organic electrochemical transistors (Viswanathan et al, 2015;Zhang C. et al, 2018;Wustoni et al, 2019;Ohayon et al, 2020). A wide range of organic molecules (polymers, small molecules, dyes, etc.)…”
Section: Methodsmentioning
confidence: 99%
“…Artificial receptors such as molecularly imprinted polymers, which have tailor-made recognition sites, represent an exciting alternative for coupling with CPs. [238,239] Due to the high complexity of the environment inside the human body and the intricate relationships between, and the body's reaction to different environmental factors, there is a need for multimodal devices that can detect a variety of biomarkers and respond to their abnormal concentrations in order to treat associated disorders. [233,240] CP-based devices such as OEIPs enable therapeutic drug delivery at a desired spatial and temporal resolution, which is of tremendous interest in biomedical research as an alternative to general drug circulation in the bloodstream.…”
Section: Outlook and Road Mapmentioning
confidence: 99%